Entry modes decisions: walmart in South Korea - Colacicco, Gianluca (2018)
Nowadays the globalization of markets has set the foundations for more integrated economic systems (Marino 2016). As inferable, firms consider of paramount importance the need to expand the geographical scope of their activities so as to take advantage of opportunities given by foreign markets. The international expansion is one of the greatest challenges faced by the modern enterprise and when firms contemplate the possibility to expand internationally, three main decisions must be carefully addressed, specifically which markets to enter, the time of entrance (early or late entrance) and the entry mode, which, if chosen properly, can be the starting point for the overall success in foreign markets. To address the topic, the research will analyze the venture of Walmart in South Korea, from which it was forced to withdraw following a series of wrong strategic decisions. Contrary to the destiny of Walmart and other retailers, the British retailer Tesco experienced an outstanding success in the same market. Based on the different outcomes, the research will attempt to investigate the factors that contributed to the failure of Walmart and to the success of Tesco in South Korea.